Stress and Vascular Responses: Oxidative Stress and Endothelial Dysfunction in the Insulin-Resistant State - Kazuya Shinozaki; Atsunori Kashiwagi; Masahiro Masada; Tomio Okamura (Elsevier, 2003)
Although insulin-resistant states have been associated with endothelial dysfunction due to increased vascular oxidative stress, the underlying mechanisms are pooly understood. Recent experimental evidence suggests that tetrahydrobiopterin (BH4), the natural and essential cofactor of NO synthases (NOS), plays a crucial role not only in increasing the rate of NO generation by NOS but also in controlling the formation of superoxide anion (O2-) in endothelial cells. Because insulin resistance has been suggested to be a significant contributing factor in the development of abnormal pteridine metabolism and endothelial dysfunction, we investivated pteridine content and NO/O2- production with the use of isolated thoracic aortas obtained from fructose-induced insulin-resistant rats. Under insulin-resistant conditions where BH4 levels are suboptimal, the production of O2- by NOS leads to endothelial dysfunction. Furthermore, oral supplementation of BH4 restores endothelial function and relieved oxidative tissue damage, at least in part, through activation of endothelial NOS (eNOS) in the aorta of insulin-resistant rats. These results indicate that insulin resistance may be a pathogenic factor for endothelial dysfunction through impaired eNOS activity and increased oxidative breakdown of NO due to enhanced formation of O2-, which are caused by relative deficiency of BH4 in vascular endothelial cells.